2016
DOI: 10.1049/mnl.2015.0309
|View full text |Cite
|
Sign up to set email alerts
|

Fracture mechanism of movable part in micro‐electro‐mechanical systems device based on empirical electron theory

Abstract: The fracture of movable part is a serious issue in micro-electro-mechanical systems (MEMS) device application. However, its fracture mechanism is not clear yet. The fracture mechanism of movable part based on empirical electron theory (EET) of solids and molecules, in which fracture model is built based on valence electron structure and broken bond of the crystal plane is clarified. Simulation and test results match EET-fracture model quite well with low errors of 8.22 and 5.95%, respectively, which shows a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The major damping source of MEMS devices is the squeeze film effect, which has nonlinearity with respect to the displacement of the device and can be influenced by packaging leaking [10]. MEMS devices utilise mechanical cantilevers as springs [11]. The stiffness of the cantilevers has good linearities when the bending motion is small.…”
Section: Kinematics Of Ppasmentioning
confidence: 99%
See 1 more Smart Citation
“…The major damping source of MEMS devices is the squeeze film effect, which has nonlinearity with respect to the displacement of the device and can be influenced by packaging leaking [10]. MEMS devices utilise mechanical cantilevers as springs [11]. The stiffness of the cantilevers has good linearities when the bending motion is small.…”
Section: Kinematics Of Ppasmentioning
confidence: 99%
“…MEMS devices utilise mechanical cantilevers as springs [11]. The stiffness of the cantilevers has good linearities when the bending motion is small.…”
Section: Challenges For Mems Damping Controlmentioning
confidence: 99%
“…Traditional S & A devices can accomplish the safety and arming functions of a fuse, however, this is not available for modern weapon because of its large size, low accuracy, and poor anti-overload capability [ 7 , 8 , 9 , 10 ]. The miniaturization of the S & A device for fuses contributes a lot to the system control of munitions, because weapons with S & A devices of a smaller size can provide more space for other devices [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the U.S. fuze annual conferences reported that the performance of on-chip-based S&A device is tested using the missile warhead at present [26][27][28][29][30], and the development trend of fuze technology is on-chip integration of machinery, electronics and pyrotechnics in the future. On this basis, our term developed a MEMS S&A device used in small-caliber ammunition innovatively, and the concrete structure as shown in Figure 2 [31][32][33]. The size of the device isΦ14×15 mm (except detonating tube, electric detonator and electric thruster).…”
Section: Introductionmentioning
confidence: 99%